ANALISIS KEPEMIMPINAN ABDUL MALIK FADJAR DALAM MEMBESARKAN UNIVERSITAS MUHAMMADIYAH MALANG - Shofwan, Arif Muzayin (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2024)
The size and size of a university cannot be separated from its leadership. This research analyzes the leadership of Abdul Malik Fadjar, namely a leader who has succeeded in growing the University of Muhammadiyah Malang (UMM) to become the largest private university in Eastern Indonesia. The data analysis technique uses content analysis by sorting things according to the focus and objectives of the research. This research found that the first step taken by Abdul Malik Fadjar and his colleagues was to formulate big ideas or ideals that had dimensions far into the future. After obtaining this picture, we then carry out stages in managing higher education, namely the consolidation stage, physical development stage, and academic development stage. The consolidation stage aims to concentrate all potential and eliminate all challenges and obstacles in order to achieve the desired goals, which includes three aspects, ideal consolidation, structural consolidation, and personal consolidation. The physical development stage was carried out by borrowing money from the bank, then remodeling the simple campus into a magnificent three-story campus, and acquiring land for future campus expansion. The academic development stage is carried out by creating a program to improve the quality of lecturers, recruiting permanent lecturers, and conducting a large-scale hunt for permanent lecturers through the Service Bond Allowance (TID) route to save campus costs.